Critical analysis of international law failures in the Russian invasion of Ukraine: implications for global security - A. Patel; R. Tiwari (Law and Safety)
This paper offers a critical analysis of the structural deficiencies in international law that Russia’s full-scale invasion of Ukraine revealed in 2022. The study reveals a significant failure of international legal mechanisms, in particular the United Nations, to effectively deter Russian aggression and prevent the escalation of violence. Despite numerous legal actions and international responses – including resolutions by the United Nations General Assembly, proceedings at the International Court of Justice and investigations by the International Criminal Court – these measures have failed to alter Russia’s conduct or prevent further deterioration of the situation in Ukraine.